2015
DOI: 10.1227/neu.0000000000000845
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Age, Anatomic Location, and Extent of Resection Influence Outcomes in Children With High-grade Glioma

Abstract: OS was significantly correlated with the location of the tumor and the extent of resection. GTR significantly improved overall survival for both glioblastoma multiforme and anaplastic astrocytoma patients, and female patients showed a much larger survival benefit from GTR than male patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 23 publications
3
43
0
Order By: Relevance
“…Temozolomide treatment is more effective in female compared to male GBM patients Sex differences in GBM incidence have been repeatedly reported (5,(7)(8)(9)(10)(11). Moreover, several recent studies have suggested that being female is associated with better outcome from GBM in both adults and children (8)(9)(10)19). The introduction of temozolomide as a component of tri-modal care for adults with GBM has improved outcomes somewhat and highlighted factors, like MGMT promoter methylation, that significantly impact on response and survival (20,21).…”
Section: Resultsmentioning
confidence: 99%
“…Temozolomide treatment is more effective in female compared to male GBM patients Sex differences in GBM incidence have been repeatedly reported (5,(7)(8)(9)(10)(11). Moreover, several recent studies have suggested that being female is associated with better outcome from GBM in both adults and children (8)(9)(10)19). The introduction of temozolomide as a component of tri-modal care for adults with GBM has improved outcomes somewhat and highlighted factors, like MGMT promoter methylation, that significantly impact on response and survival (20,21).…”
Section: Resultsmentioning
confidence: 99%
“…Gliomas constitute 60% of all primary brain tumors [26]. The maximum resection of the tumor remains the key point in the management of gliomas with a direct influence on the survival of patients [23]. The progress made over the last two decades in surgical techniques including microsurgery by the operating microscope, preoperative functional imaging (e.g., functional MRI, MRI tractography), intraoperative electrical stimulation in awakened craniotomy and intraoperative imaging (surgery guided by real-time imaging using neuronavigation or intraoperative MRI) have largely contributed to significantly increase resected tumor volume while improving morbidity and mortality [33].…”
Section: Introductionmentioning
confidence: 99%
“…For example, boys constitute the majority of group 3 and 4 medulloblastomas, with peak incidences less than 5 years of age and in the peripubertal period (10,11). Moreover, boys with high-grade gliomas have significantly reduced overall and progression-free survival relative to girls (12). These findings suggest that existing sex disparities, at least in the case of brain cancers, are not completely attributable to the actions of circulating sex hormones.…”
Section: Introductionmentioning
confidence: 99%